Automated Ribotyping Using Different Enzymes To Improve Discrimination of Listeria monocytogenes Isolates, with a Particular Focus on Serotype 4b Strains - De Cesare, Alessandra (American Society for Microbiology, 2001)
To develop improved automated subtyping approaches for Listeria monocytogenes, we characterized the discriminatory power of different restriction enzymes for ribotyping. When 15 different restriction enzymes were used for automated ribotyping of 16 selected L. monocytogenes isolates, the restriction enzymes EcoRI, PvuII, and XhoI showed high discriminatory ability (Simpson's index of discrimination > 0.900) and produced complete and reproducible restriction cut patterns. These three enzymes were thus evaluated for their ability to differentiate among isolates representing the two major serotype 4b epidemic clones, those having ribotype reference pattern DUP-1038 (51 isolates) and those having pattern DUP-1042 (20 isolates). Among these isolates, PvuII provided the highest discrimination for a single enzyme (nine different subtypes; index of discrimination = 0.518). A combination of PvuII and XhoI showed the highest discriminatory ability (index of discrimination = 0.590) for these isolates. A group of 44 DUP-1038 isolates and a group of 12 DUP-1042 isolates were identical to each other even when the combined data for all three enzymes were used. We conclude that automated ribotyping using different enzymes allows improved discrimination of L. monocytogenes isolates, including epidemic serotype 4b strains. We furthermore confirm that most of the isolates representing the genotypes linked to the two major epidemic L. monocytogenes clonal groups form two genetically homogeneous groups.